Effectiveness of Providing Remuneration Allowances for State Civil Apparatus in Bapas Class I Manado - Derek, Blandina Astrilyen; Masengi, Evi; Tumbel, Goinpeace (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine the effectiveness of providing remuneration allowances for State Civil Apparatus at Bapas Kelas I Manado and the obstacles in implementing the policy.  The research method used was descriptive qualitative research method and sought the necessary data by means of observation, interview and document study at Bapas Kelas 1 Manado. The results of the research found that the provision of humeneration is very helpful for employees in meeting their needs. Remuneration for civil servants is an objective solution in overcoming the low income of civil servants because one of the criteria for granting it is based on work performance. There needs to be more supervision of the provision of remuneration because there are still many abuses of authority on performance reports.